4-p2=p2+2

Subtract p2 from both sides of the equation.

4-p2-p2=2

Subtract p2 from -p2.

4-2p2=2

4-2p2=2

Subtract 4 from both sides of the equation.

-2p2=2-4

Subtract 4 from 2.

-2p2=-2

-2p2=-2

Divide each term in -2p2=-2 by -2.

-2p2-2=-2-2

Cancel the common factor of -2.

Cancel the common factor.

-2p2-2=-2-2

Divide p2 by 1.

p2=-2-2

p2=-2-2

Divide -2 by -2.

p2=1

p2=1

Take the square root of both sides of the equation to eliminate the exponent on the left side.

p=±1

Any root of 1 is 1.

p=±1

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

p=1

Next, use the negative value of the ± to find the second solution.

p=-1

The complete solution is the result of both the positive and negative portions of the solution.

p=1,-1

p=1,-1

p=1,-1

Solve for p 4-p^2=p^2+2